Transcatheter treatment of native aortic valve regurgitation: Results from an international registry using the transfemoral ACURATE neo valve - Purita, Paola Angela Maria (Int J Cardiol Heart Vasc, 2020)
BACKGROUND: Transcatheter aortic valve replacement (TAVR) has been validated for the treatment of severe symptomatic aortic stenosis in patients at high and intermediate surgical risk. Recently, TAVR has been proposed as an alternative to medical therapy in inoperable patients with severe native aortic valve regurgitation (NAVR). This multicenter international registry sought to evaluate safety and efficacy of TAVR with the self-expandable ACURATE neo valve in a cohort of patients with NAVR. METHODS: A total of 24 patients with severe NAVR treated by TAVR between September 2016 and October 2018 in 13 European centers were included. Clinical, procedural and follow up data were inserted in a dedicated database. Outcomes were codified according to Valve Academic Research Consortium-2 criteria. RESULTS: Mean age was 79.4 years, 58.4% were female. Mean EuroSCORE II and STS score were 5% and 3.9%, respectively. Device success was 87.5%. Moderate paravalvular leak (PVL) was found in two (8.3%) of patients, both with a perimeter oversizing index <10%. Implantation of a second device was necessary in three cases (12.5%), one for severe PVL and two for device displacement. New pacemaker implantation rate was 21.1%. At 30 days, stroke and all-cause mortality rates were 0% and 4.1%, respectively. CONCLUSIONS: This multicenter study suggests good feasibility and early safety of transfemoral TAVR with the self-expandable ACURATE neo device in patients with severe NAVR refused for surgery. Rates of moderate PVL, new pacemaker implantation and need for a second valve were higher than those reported for TAVR in aortic stenosis.